Blackboard@ LMS for blended learning: Students’ views versus staff views on challenges and improvement - Mohammed O. A. Mohammed; Muhanad El Hag; Mohamed A. E. M. Ibrahim; Javed Khan (Knowledge Management & E-Learning: An International Journal)
The Blended learning system (BELS) has become a popular tool of learning. BELS’s effectiveness is substantially influenced by a number of elements, including teacher and student feedback and system design. This study on evaluating the Blackboard platform (removed for peer review) aims to determine the similarity between students’ and faculty members’ perspectives, identify the least satisfied elements of learning that need improvement, and collect suggestions for future enhancements. Using the SurveyMonkey service, questionnaires were sent directly to the emails of students and faculty members at the four colleges of the university. There were 1170 responses from students and 93 responses from staff members. SAS JMP was used to perform Linear Discriminant Analysis (LDA) to show the relationships between academic staff perceptions and their recommendations from one side and the students’ perceptions and satisfactions distributed by colleges from another side, while SPSS was used to visualize the data. Students and faculty were highly satisfied with blended learning and high expectations for its effectiveness The perceptions of faculty members were similar to those of students; however, they were more satisfied with certain features than students were. The LDA results of staff survey demonstrated that the responses of faculty members vary by college, unlike the LDA for students’ survey that did no show between-college variations. This implies that, students across colleges have similar needs and common attitudes toward BEL. Students were least satisfied with peer interactions; online IT assistance; the development of skills using current students’ activities; and the update frequency and quality of online content. We advocate incorporating student perspectives into plans and considering faculty members’ suggestions particularly for increasing peer-to-peer learning; in-line translation and use of infographics.